2009
DOI: 10.1080/08998280.2009.11928463
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Toxoplasmosis in a Patient with Undiagnosed Aids

Abstract: Approximately 60% of deaths in patients with AIDS are a direct result of infection other than HIV. The more severe and life-threatening complications of HIV infection occur in patients with a CD4(+) T cell count <200 cells/μL. In the absence of effective retroviral therapy, these infections are associated with a high mortality. We describe a case of disseminated toxoplasmosis discovered at autopsy in a patient with undiagnosed AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
1
2
0
1
Order By: Relevance
“…A similar patient has been reported in the literature with presence of disseminated toxoplasmosis, CMV adrenalitis, and PJP [26]. However, the presentations of all these infections were typical in that case.…”
Section: Discussionsupporting
confidence: 82%
“…A similar patient has been reported in the literature with presence of disseminated toxoplasmosis, CMV adrenalitis, and PJP [26]. However, the presentations of all these infections were typical in that case.…”
Section: Discussionsupporting
confidence: 82%
“…Antemortem diagnosis is rare with only a handful of cases ever described [10]. When gastrointestinal toxoplasmosis has been identified, the most common underlying risk factor has been severe immunosuppression, with a CD4 count < 60 cells/ μ L [4, 5, 11]. Previous studies have found between 6.5% and 9.7% of all AIDS patients to have evidence of gastrointestinal toxoplasmosis at time of autopsy [9, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Complete or partial involvement of the gastrointestinal tract may be present [ 15 ]. If toxoplasmosis is suspected, biopsies are necessary as disseminated toxoplasmosis is almost invariably fatal if left untreated [ 11 , 16 ]. The most common endoscopic findings of gastrointestinal toxoplasmosis are thickened gastric folds, ulcerative lesions, and nonspecific inflammation [ 4 , 14 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 En este último caso las infecciones tienden a ser diseminadas y puede significar la causa final de lesiones muy graves e incluso la muerte. 6 Por la tendencia hacia los estados crónicos o latentes de esta enfermedad en Costa Rica, no se le da mucha importancia a diferencia de otros países en que normalmente se realizan estudios de tipo epidemiológico, inmunológico y patológico. 7 Así, se tienen estudios de prevalencia con alguna regularidad en muchos países 1 e inclusive en regiones europeas.…”
unclassified